Classroom displays about The Netherlands - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a girl seated at a slide projector in a classroom. On the blackboard is a hand-drawn map of the Netherlands. A doll in traditional Dutch dress leans against a diorama representing the Dutch countryside.